Republic of Madagascar : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision, and Anti-Money Laundering. (IMF Staff Country Reports; Country Report ;, 2006)
The insurance sector is underdeveloped and has been inadequately supervised to date, as the regulator lacks the requisite independence, skills, and resources. The three public pension systems, which cover less than 10 percent of the active population, appear to be fiscally unsustainable. The banking regulatory and supervisory framework is broadly adequate, although implementation and enforcement need further strengthening. The weak financial position of the Central Bank of Madagascar (BCM) could undermine macroeconomic and financial policies and contribute to economic and financial instability.